Hermite-Hadamard Inequalities via Riemann-Liouville Fractional Integrals with Generalized Convex Functions (European Journal of Pure and Applied Mathematics, 2025)
In this study, novel fractional integral inequalities for twice-differentiable geometrically arithmetically $(α, m)$-convex functions are presented. The classical Riemann-Liouville fractional integrals are used to obtain several new identities. By employing the above convexity, Hermite-Hadamard type inequalities are investigated using these identities. The main findings of this work extend the existing literature and are derived as special cases.